Sumber Pendapatan Istri Petani Dan Kontribusinya dalam Rumah Tangga: Sebuah Analisis Ekonomi - Akbar; Syafiuddin; Putri, Wiraksini Tri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2024)
The wife's contribution to the family is unavoidable. In addition to preparing the husband's needs before and after he comes home from work, as well as taking care of all household needs, the wife's responsibility is working to help the husband in meeting the needs of his household. The purpose of this study was to determine the income of farmer households, the source of income of farmer wives, and their contribution to the household. This study was carried out in Manongkoki Village, North Polongbangkeng District, Takalar Regency, in May and June 2023. In this study, 125 farmer's wives who worked outside the home were included. The sample used was 25% of the population so that the number of samples used in this study was 31 people. The sampling technique used is simple random sampling. This research uses a qualitative approach with a case study method. The data collection techniques used were observation and interviews using questionnaires. The data analysis techniques used were income analysis and income contribution analyses. The findings revealed that (1) the average household income was IDR 2,090,412 per month, (2) the sources of income for farmers' wives were farm laborers, traditional cake sellers, and grocery traders, and (3) farmers' wives contributed 34% of home income with a low category. Farming families appreciate this revenue contribution since it allows them to cove.